Answer:
x=8.
Explanation:
For triangle GTL
h²=p²+b²
or, 13²=p²+12²
or, 169=p²+144
or, p²= 25
or, p=5
so, GT = 5
now
for triangles GTL and GTJ
<GTL=<GTJ(both are 90° because GT is perpendicular to JL)
<JGT=<LGT=90° (GT is perpendicular to JL so it bisects G)
GT=GT(common)
so
triangles GTL and GTJ is congruent by A.S.A axiom
JT=12(correspong side of congruent ttriangle are equal)
now
JG= 13(corresponding side of congruent triangles are equal)
now
for triangle JGT, it is a right angled triangle as <JGT = 90°)
Let <JGT be G.
tanG=p/b
or, tanG=12/5
G= 67.4°
<JGT=67.4°
now
<JGR=<JGT=67.4°(JG is at midpoint bisecting <RGT)
in JGR,
<JRG=90°(RG is perpendicular to JK as <GRK is 90°)
now
JGR is a right angled triangle so
cosG=b/h
or, cos67.4=(x-3)/13
or, cos67.4(13)=x-3
or, 4.99=x-3
or, 5 = x-3
so, x = 5+3
so, x = 8